The significance of the Qur’anic evidence in Mutammimat Al-Ajrumiyya by Shaykh al-Hattab - Asem Shehadeh Ali,; Mohammad Ahmad Qudah,; Luqman Hakim Azmi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research aims to present the opinions of scholars on the use of Qur’anic evidence for grammatical significance in Arabic grammar, and to clarify some of the secrets of the Holy Qur’an through the rules of Arabic grammar, and to reveal the way of thinking and writing of Shaykh al-Hattab in writing the rules of the Arabic language, and to identify the methodology that he uses in facilitating learning Arabic grammar. The study follows the descriptive and the analytical methodology, as it will focus on observing and analysing the use of the significance of the Qur’anic evidence found in the book “Mutammimat al-‘Ujrumiyyyah” by al-Hattab. The study reached important results, including: This study finds that Shaykh Al-Hattab used Qur’anic evidence extensively in his book in all sections of grammar, especially in the chapter on relative nouns, and he included some evidence that he wrote himself, and he also recited some poetic verses as a citation for specific issues. The discussion of the Qur’anic evidence, especially in the chapter on the relative pronoun, still needs in-depth research and focus because there is some significance that was not mentioned in this study. The study found that Shaykh al-Hattab had brought evidence of his own that was not found in the the book of Mutammimat al-‘Ujrumiyyyah.